El desarrollo de una metodología híbrida para el estudio de las prácticas comunicativas en las regiones fronterizas de América del Sur - Husum, Jonathan Mastai (Diálogos Latinoamericanos, 2023)
When we as new researchers embark on our first field research stay, we often face the challenge of bridging the gap between the project’s research design and the practical fieldwork. Drawing from my experiences in collecting data for my doctoral project, this article emphasizes the adaptability needed to adjust research designs as new knowledge emerges. More specifically, it also caters to those interested in conducting qualitative sociolinguistic research to gather data on the usage of contact languages. This article sheds light on my research design, primarily focusing on empirical data collection related to communicative practices in South American Portuñol and other languages in five border regions. It argues that the effective study of Portuñol practices across diverse borders requires consistent data collection methods that promote triangulation. Proposed methods are sociolinguistic interviews, documenting the linguistic landscape, and analysing official documents to comprehensively understand the regions’ diverse sociolinguistic behaviors.